Fabrication of Porous Polyimide Membrane with Through‐Hole via Multiple Solvent Displacement Method - Hirai, Sho (ChemistryOpen, 2021)
Porous polyimide (PI) membranes are widely used in separation processes because of their excellent thermal and mechanical properties. However, the applications of porous PI membranes are limited in the nanofiltration range. In this study, porous PI membranes with through‐holes have been successfully fabricated by the novel multiple solvent displacement method. This new method requires only a porous polyamic acid (PAA) membrane, which was prepared by immersing PAA film in N‐methylpyrrolidoneebk; (NMP) prior to immersing it in a mixed solvent consisting of NMP and a poor solvent, followed by immersion only in poor solvent. The pore size, morphology, porosity, and air permeability demonstrated that the fabricated PI membranes had a uniformly porous structure with through‐holes over their surface. This new method enabled control of pore size (3–11 μm) by selecting a suitable poor solvent. This multiple solvent displacement method is highly versatile and promising for the fabrication of porous PI membranes.